Recent advances in nanogels in veterinary medicine - Soriano Perez, María Laura (2025)
Nanogels, a promising class of nanomaterials, have emerged as versatile platforms in veterinary medicine and have shown substantial progress in recent years. This review outlines the key developments and potential applications of nanogels in veterinary therapeutics. It provides an in-depth discussion of critical factors influencing nanogel implementation, including synthesis, biocompatibility, biodegradability, clinical translation, and technological considerations. Approaches to nanogel-based vaccines and drug-delivery systems are examined, with particular emphasis on the mucosal route of administration, given its relevance in livestock. Finally, the integration of nanogels into the One Health framework is considered.